Near-real-time combustion monitoring for PCDD/PCDF indicators by GC-REMPI-TOFMS - Gullett, Brian K; Oudejans, Lukas; Tabor, Dennis; Touati, Abderrahmane; Ryan, Shawn (Environmental science & technology, 2012)
The boiler exit flue gas of a municipal waste combustor was sampled to evaluate an online monitoring system for chlorobenzene congeners as indicators of polychlorinated dibenzodioxin and dibenzofuran (PCDD/PCDF) concentrations. Continuous measurements of chlorobenzene congeners using gas chromatography coupled to a resonance-enhanced multiphoton ionization - time-of-flight mass spectrometry (GC-REMPI-TOFMS) system were compared over 5-min periods with conventional sampling methods for PCDD/PCDF. Three pairs of values were taken every hour over a period of three days to characterize the combustor's response to transient operating conditions (shutdowns and startups). Isolation of specific chlorobenzene congeners from other same-mass compounds was accomplished by using a GC column separator ahead of the REMPI-TOFMS. The 50-fold variation of PCDD/PCDF concentration was paralleled by similar changes in monitored compounds of 1,4-dichlorobenzene, 1,2,4-trichlorobenzene, 1,2,3-trichlorobenzene, and 1,2,4,5-tetrachlorobenzene. A correlation of R = 0.85 and 0.89 was established between 40 pairs of simultaneous 5-min GC-REMPI-TOFMS measurements of 1,2,4-trichlorobenzene and 5 min conventional sampling and analysis for the TEQ and Total measures of PCDD/PCDF, respectively. The GC-REMPI-TOFMS system can be used to provide frequent measures of correlative PCDD/PCDF concentration thereby allowing for an understanding of measures to minimize PCDD/PCDF formation and develop operational feedback to limit emissions.